Tindak Tutur dalam Pidato Bangtan Sonyeondan di United Nations General Assembly - Fathiya, Nurul; Revita, Ike; Aslinda, Aslinda (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
This research is about speech acts in a speech by Bangtan Sonyeondan at the United Nations General Assembly (UNGA) which aims to identify and describe the classification of speech acts contained in BTS speeches. The data from this qualitative descriptive research were obtained from 3 videos of BTS's speeches with UNICEF through the official UNICEF Youtube channel. Data were analyzed using the equivalent method. The results showed that there were four speech act classification categories found in this study, namely, representative, directive, commissive and expressive. Representative actions convey many facts about life during Covid-19. These speech acts are most commonly found in their speeches. From the utterances found, it explains a lot about the facts and the utterances conveyed. Directive speech acts ask speech partners to make changes and provide motivation for life during a pandemic. Commissive speech acts provide the ability to change a better life. Then, the expressive speech act uttered as an evaluation of changes and expectations from the speech was conveyed by BTS.